2016
DOI: 10.1007/978-3-319-41342-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin and Its Role in Chronic Diseases

Abstract: Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone) is a plant-derived naphthoquinones obtained mainly from three families, including Plumbaginaceae, Droseraceae, and Ebenaceae. Plumbagin has exhibited its potential therapeutic benefits on numerous chronic diseases, i.e., breast cancer, non-small cell lung cancer, melanoma, ovarian, squamous cell carcinomas, pancreatic cancer, and prostate cancer. In addition, its anti-inflammatory and antimicrobial activities as well as control of diabetes and cardiovascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), a natural-derived naphthoquinone, isolated from the roots of Plumbaginaceae plants (Checker et al, 2018), has been reported to have anticancer effect in various types of cancer, including breast, lung, prostate, cervical, liver, colon, brain, and melanoma cancers (Panichayupakaranant & Ahmad, 2016;Rajalakshmi et al, 2018;Checker et al, 2018). These anticancer effects are mediated through the modulation of cellular redox balance and reduction of glutathione levels, as well as through the activation of apoptotic pathways in cancer cells (Checker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), a natural-derived naphthoquinone, isolated from the roots of Plumbaginaceae plants (Checker et al, 2018), has been reported to have anticancer effect in various types of cancer, including breast, lung, prostate, cervical, liver, colon, brain, and melanoma cancers (Panichayupakaranant & Ahmad, 2016;Rajalakshmi et al, 2018;Checker et al, 2018). These anticancer effects are mediated through the modulation of cellular redox balance and reduction of glutathione levels, as well as through the activation of apoptotic pathways in cancer cells (Checker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin-loaded PLGA core-shell nanoparticles have been found to reach complete release within 24 h 14 . For treating chronic diseases such as diabetes, long-term drug delivery, in the range from weeks to months or even longer, is important for patient compliance 1 , 15 , 16 . The relatively fast release rates of polymer nanoparticles are not suitable for long-term drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Plumbagin ( Figure 1A) is a naturally occurring 1,4-naphthoquinone and analogue of vitamin K3 isolated from plants of the Plumbaginaceae, Droseraceae, and Ebenaceae families. [1,2] Purified plumbagin inhibits the proliferation of various types of cancer cells, as reviewed extensively in, [3,4] therefore it is considered a valid oncology drug candidate. In vivo studies have shown that it reduces primary tumor burden across cancer types as measured by tumor growth rate as well as tumor weight and volume.…”
Section: Introductionmentioning
confidence: 99%